1976
DOI: 10.1159/000207947
|View full text |Cite
|
Sign up to set email alerts
|

Hb Helsinki: a Variant with a High Oxygen Affinity and a Substitution at a 2,3-DPG Binding Site (<i>β</i>82 [EF6] Lys→Met)

Abstract: A new haemoglobin, Hb Helsinki, in which β82-Lys (EF6) is replaced by Met, was found in a Finnish family. It was associated with familial erythrocytosis, and the oxygen affinity of the blood was higher than normal. The oxygen equilibrium curves of purified Hb Helsinki and HbA from the same haemolysate have been determined under various conditions. ‘Stripped’ Hb Helsinki was found to show normal cooperativity, slightly low oxygen affinity and a reduced Bohr effect at physiological pH. However, the organic phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Since the discovery of the role of 2,3-diphosphoglycerate (DPG)' in regulating oxygen transport (1,2) led to the identification of the binding sites ofanionic cofactors in the hemoglobin molecule (3,4), an understanding of linkage between oxygen binding and cofactor binding has been sought through studies on hemoglobin variants with alterations at the 2,3-DPG binding site (5)(6)(7)(8)(9). Recently Perutz and Poyart (10) reported that low molecular weight compounds, such as 2-(4-chlorophenoxy)-2-methylpropionic acid (clofibric acid) and 2-[4-(2-p-chlorobenzamidethyl)-phenoxy]-2-methylpropionic acid (bezafibrate), have the remarkable ability to modify hemoglobin function in erythrocytes, a finding that opened the way to studies ofthe molecular control of hemoglobin function and its clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of the role of 2,3-diphosphoglycerate (DPG)' in regulating oxygen transport (1,2) led to the identification of the binding sites ofanionic cofactors in the hemoglobin molecule (3,4), an understanding of linkage between oxygen binding and cofactor binding has been sought through studies on hemoglobin variants with alterations at the 2,3-DPG binding site (5)(6)(7)(8)(9). Recently Perutz and Poyart (10) reported that low molecular weight compounds, such as 2-(4-chlorophenoxy)-2-methylpropionic acid (clofibric acid) and 2-[4-(2-p-chlorobenzamidethyl)-phenoxy]-2-methylpropionic acid (bezafibrate), have the remarkable ability to modify hemoglobin function in erythrocytes, a finding that opened the way to studies ofthe molecular control of hemoglobin function and its clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Presumably arising from this indispensable role in DPG binding, this residue is uniformly conserved in mammalian Hbs (Fig. 3A), with the exception of several heterozygous adult human HbA carriers with substitutions at this position (18,19,31).…”
Section: Resultsmentioning
confidence: 99%
“…1B). This replacement is intriguing not only because β82Lys is invariant among known mammalian Hbs, but because human variants with substitutions at this position display profound alterations in both structural and functional properties [16][17][18][19] . The human Hb Providence (β82Lys→Asn) variant in particular has been well characterized as asparagine at this position progressively undergoes posttranslational deamidation to form aspartic acid (Asp), which over the life-time of the erythrocyte, constitutes ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these patients, some carry Hb Helsinki [1] whose structure-function rela tionship has been fully elucidated, whereas others carry hemoglobins whose structures are still un known.…”
mentioning
confidence: 99%